UPAYA MENINGKATKAN MOTIVASI BELAJAR IPS DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA SISWA KELAS IV SDN JABRES KECAMATAN SRUWENG KEBUMEN - Bagas Setiawan (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2014)
This study aims to improve learning motivation in social science through Jigsaw cooperative learning model to fourth grade students of SDN Jabres, Sruweng subdistrict, Kebumen district.This research is a classroom action research undertaken collaboratively. Design of this study  using model of Kemmis and Taggart consisting of 3 cycles. Subject in this study were fourth  grade students of SDN Jabres, Sruweng subdistrict, Kebumen district total of 32 students  consisting of 14 male students and 18 female students. Data was collected by questionnaires,  observations and field notes. Quantitative data was analyzed using descriptive statistic and Qualitative data using flow model. The result showed that after application of the Jigsaw method of learning can improve  learning motivation in social science. It was marked by an increased percentage of the  average number of learning motivation in pre action there was 19%, in the first cycle 53%, in  the second cycle 78% and 94% in the third cycle. Based on the results of research conducted,  researcher advises schools or teachers can improve the students’ motivation and apply the  Jigsaw model on learning.